On Certain New Subclass of Sakaguchi Type Function Related to Sigmoid Functions - Srutha Keerthi, B.; Revathi, M. (International Journal of Engineering and Technology, 2018)
The object of the present paper is to obtain initial coefficients | |,| |,| |, upper bounds of | | and second Hankel determinant associated with a class of analytic univalent function of sakaguchiÂ type function related to sigmoid function in the open unit disc âˆ†. Various authors as Abiodum, Tinuoye Oladipo, Murugusundaramoorthy et. al., and Olatunji have studied sigmoid function for different classes of analytic and univalent functions. Our results serves as a generalisation in this direction and it gives birth some existing subclasses of functions.Â